2018
DOI: 10.1007/s40617-018-0264-6
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Management in Self-Contained Classrooms for Children with Autism: Extending Research on the Color Wheel System

Abstract: The color wheel is an evidence-based classroom management system that has been used to decrease inappropriate behaviors and increase on-task behaviors in general education elementary classrooms but not in classrooms for students with autism spectrum disorder (ASD). A multiple-baseline design was used to evaluate the effects of the color wheel system (CWS) on disruptive behaviors (being out of seat for one classroom, inappropriate vocalizations for two classrooms) in three self-contained elementary classrooms f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…These results are consistent with previous findings in which the implementation of the CWS increased on-task behavior for students without disabilities (Fudge et al, 2008; Blondin et al, 2012). Although previous studies have shown the effects of the CWS on decreasing inappropriate behavior of students with autism (Aspiranti et al, 2018, 2019), this is the first study to examine the CWS effects on increasing on-task behavior for students with various disabilities (specific learning disabilities, other health impairments, autism, and intellectual disability) in inclusion classrooms.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…These results are consistent with previous findings in which the implementation of the CWS increased on-task behavior for students without disabilities (Fudge et al, 2008; Blondin et al, 2012). Although previous studies have shown the effects of the CWS on decreasing inappropriate behavior of students with autism (Aspiranti et al, 2018, 2019), this is the first study to examine the CWS effects on increasing on-task behavior for students with various disabilities (specific learning disabilities, other health impairments, autism, and intellectual disability) in inclusion classrooms.…”
Section: Discussionmentioning
confidence: 94%
“…Acceptability data were collected from all teachers at the completion of the study. Teacher acceptability data were gathered through a 10-item Likert scale that has been previously used in CWS research with scores ranging from 1 (strongly disagree) to 6 (strongly agree) (Watson et al, 2016; Aspiranti et al, 2019). The teachers chose to complete the acceptability measure as a team; therefore, all answers are provided for the teacher team.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the implementation of the CWS during PE classes followed the guidelines set forth by Skinner et al (2007). The CWS is widely recognized as a cost‐effective intervention that utilizes visual stimuli, specifically colors, to enforce multiple sets of rules and provide clear behavioral expectations for various activities throughout the lesson (Aspiranti et al, 2019; Blondin et al, 2012; Skinner et al, 2007; Watson et al, 2016). The verbal alerts given by the teacher, providing advance notice of upcoming transitions, allow students to wrap up their current tasks and mentally prepare for the next situation, thereby reducing the likelihood of disruptive behaviors (Codding & Smyth, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Originally developed as a behavior management system for students with emotional and behavioral disorders, the CWS has demonstrated effectiveness in managing disruptive behaviors across various educational settings . It has been successfully implemented in special education programs for students with developmental disabilities (Aspiranti et al, 2018(Aspiranti et al, , 2019(Aspiranti et al, , 2021, kindergarten environments (Watson et al, 2016), and elementary education classrooms (Blondin et al, 2012). However, the efficacy of this behavior management strategy in middle school PE classes remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%